KOMUNIKASI PEMASARAN CAFE RUANG IMAJIKU DALAM MENINGKATKAN MINAT PELANGGAN MELALUI INSTAGRAM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research aims to describe Ruang Imajiku's marketing communication strategy for increasing customer interest through Instagram as well as the features that Ruang Imajiku uses in marketing on Instagram. This research uses a qualitative method with a marketing communication approach. The source of data for this research is the owners, employees, and visitors of the Imajiku Room. Data collection techniques include observation, interviews, and documentation. The data analysis technique uses an inductive model with data reduction, data presentation, and documentation. The results of this study show that Ruang ImajiKu has succeeded in increasing customer interest through Instagram with marketing communication strategies such as regular promotions and creative content. High-quality content that is relevant to your audience's interests, as well as creativity in keeping up with the latest trends, plays an important role in their strategy. Imajiku Space also leverages Instagram features such as Snapgram, Highlights, and Reels to create engaging and interactive content. The use of these features helps increase their presence on Instagram and attract more visitors to the café. The success of this strategy can be seen from good interaction with followers and an increase in the number of visitors to the café.